The Influence of Entrepreneurship Digitalization and Literacy Strategies on the Ability of MSMES After Surviving the Middle of the Covid-19 Pandemi in Makassar City - Muh. Irshan Sachrir; Nasikh; Grisva Agustin (Jurnal Multidisiplin Madani, 2022)
This study is designed to see the effect of the independent variables, namely digitalization strategy and entrepreneurial literacy, on the dependent variable, namely the ability of MSMEs to survive in the midst of the COVID-19 pandemic, both directly and indirectly.  This research was conducted using a quantitative approach, and was designed as an explanatory study.  Respondents who are the subject of research are MSME actors in Makassar City.  The sampling technique applied is non-probability sampling using the qouta sampling method by determining the number of respondents as many as 30 people.  The analytical method used is multiple regression analysis with the help of an analytical tool, namely IBM SPSS version 25. The results of this study indicate that (1) the digitization strategy does not have a positive and partially significant effect on the ability of MSMEs to survive in the midst of the COVID-19 pandemic; (2) entrepreneurial literacy does not have a positive and significant effect partially on the survival ability of MSMEs in the midst of the COVID-19 pandemic;  and (3) digitalization strategies and entrepreneurial literacy do not simultaneously have a positive and significant effect on the ability of MSMEs to survive amid the COVID-19 pandemic